Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.3354/meps258097
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal tumor formations in the massive coral Pavona clavus

Abstract: Skeletal tumor formations in the massive coral Pavona clavus were investigated for 3 yr on the northern Pacific coast of Costa Rica in a reef composed almost exclusively of this species. A field survey of tumor incidence showed that more than half of the population presented this phenomenon and that frequencies increased with depth. Up to 37 tumors per colony were recorded, and the largest tumor size was 37.5 m 2 , covering the whole colony surface area. Tumors and healthy skeletons and tissues were studied by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 21 publications
3
34
0
1
Order By: Relevance
“…However, if no free space is available, GAs would likely overgrow healthy partners. Gateño et al (2003) observed healthy tissues overgrown by GA tissues in Porites clavus. Peters et al (1986) and Work et al (2008) reported that progressive growth of GAs in Acropora spp.…”
Section: Death and Progression Of Gasmentioning
confidence: 99%
See 3 more Smart Citations
“…However, if no free space is available, GAs would likely overgrow healthy partners. Gateño et al (2003) observed healthy tissues overgrown by GA tissues in Porites clavus. Peters et al (1986) and Work et al (2008) reported that progressive growth of GAs in Acropora spp.…”
Section: Death and Progression Of Gasmentioning
confidence: 99%
“…Higher growth rates of GAs compared to healthy tissues have been reported for Acropora formosa (Cheney 1975), A. palmata (Peters et al 1986), Platygyra pini, P. sinensis (Loya et al 1984), and Pavona clavus (Gateño et al 2003). GAs probably overgrow adjacent healthy regions using energy supplied from the adjacent tissue.…”
Section: Nutrient Supply From Healthy Regions To Gasmentioning
confidence: 99%
See 2 more Smart Citations
“…PUWS is characterized by discrete, bleached, round foci, 3 to 5 mm in diameter, that may result in ulcerations that coalesce and cause tissue loss and colony mortality (Raymundo et al 2003). Other Indo-Pacific diseases not previously observed in the Philippines include, but are not limited to, Porites pink-line syndrome (Ravindran & Raghukumar 2002) and coral tumors (Coles & Seapy 1998, Hunter 1999, Yamashiro et al 2000, Gateño et al 2003. Coral reef bleaching in the Philippines has caused acute losses of coral cover (Raymundo & Maypa 2002, Wilkinson 2002.…”
Section: Introductionmentioning
confidence: 99%